Development of a motivational-base for household waste management training model - Yayan Sudrajat (SAINTIS Publishing, 2022)
The study objective is to develop a motivation-based training model in household waste management which will result in the development of a conceptual model, the development of a procedural model, and the development of a physical model. Research and development methods (R D), a combination of the Borg and Gall development model, the Dick and Carey learning model, and the Keller Motivation Model. The instrument is validated by the validator, then the instrument that has been validated will be used for the feasibility of the product to be tested by experts consisting of instructional design experts, curriculum experts, training material experts, and instructional media experts for the feasibility of research products. Then the product was tested on several prospective trainers through one-to-one trials, small group, and field trials. The results of research by instructional design experts, training material experts, curriculum experts, and instructional media experts state that it is very good and feasible to use motivation-based household waste management training with the name SPIRIT Training Model to increase the motivation of prospective trainers in household waste management training activities so that can reduce household waste in Indonesia.